Intersectoral Linkages in Booming Sector Economies - Gomes, Sérgio Ricardo Santos; Marques, Joao Alexandre Lobo; Reis, Ricardo Ferreira (2022 13th International Conference on E-business, Management and Economics, 2022)

Investigation on citizen trust towards e-government services in GBA – A study on WeChat and Alipay government service mini-programs - Lai, Chimeng; Joao, Alexandre Lobo Marques (2022 13th International Conference on E-business, Management and Economics, 2022)
Citizens' trust in eGovernment is crucial for the successful implementation of new electronic services. This relationship in the Greater Bay Area (GBA) plays an essential role since the Government services rely on mobile mini-programs This study investigates the trust towards government service mini-programs in WeChat and Alipay. A user feedback questionnaire was designed, and a total of 609 valid samples were collected from Shenzhen, Guangzhou, Hong Kong, and Macau. The findings imply that competence, integrity, and benevolence are the key components of trust in e-government (TIEG). TIEG positively influences perceived value (PV), which positively affects citizens' Intention to adopt service mini-programs. PV significantly mediates the relationship between TIEG and Intention. Although TIEG does not effectively reduce perceived risk (PR), risk issues cannot be ignored in the adoption process. Finally, this article proposes relevant implications and suggestions for the GBA government agents and policy makers.
0 citations (Crossref) [2023-03-15]

How Social Influence and Image Impact on the Intention to Use a Technology: A Study from the Battery Electric Vehicle Domain - Lampo, Alessandro; Silva, Susana C. (2022 13th International Conference on E-business, Management and Economics, 2022)
Technology research offers several theories and models to explain how individuals accept and use technology innovations. While these often focus on the technical aspects of the innovation, they tend to downplay the affective component of technology. Recognizing that the adoption of technology is also determined by what it means and represents to the users, this paper aims to fill the gap in the literature by studying the effects of social influence and image on the behavioral intention to adopt a technology. We used structural equation modeling (SmartPLS) to analyze data collected from 238 self-administrated surveys regarding the behavioral intention of Macau residents to use battery electric vehicles. The result showed significant relationships among the variables in the model and depicted the construct of image as a strong factor in the adoption decision. Our findings suggest that social influence may not exhibit substantial impact in the case of innovations in their initial phase and, more importantly, the construct of image could be included as a key predictor of behavioral intention in technology acceptance models, particularly in contexts where the choices that consumers make are public, and therefore subject to judgments from the members of the community.
Best Oral Presentation Award: https://www.usj.edu.mo/en/news/dr-alessandro-lampo-receives-best-oral-presentation-award-at-the-iceme-2022/
Keywords: Battery Electric Vehicles; Image; SmartPLS; Social Influence; Technology Acceptance

Economic Integration in the GBA: a Price-Based Assessment of Real and Financial Integration in the Greater Bay Area - Lei, Weng Chi; Wang, Xinru (2022 13th International Conference on E-business, Management and Economics, 2022)
The Guangdong-Hong Kong-Macau Greater Bay Area (GBA) was first conceptualized in 2016, which aimed to facilitate trade and finance liberalization among the three regions. The trade and financial environment of the GBA is unique. Due to the “one country, two systems” principle, Mainland China, Hong Kong and Macau are considered to be trading partners bounded by WTO rule, but bilateral free trade agreements have been signed between Mainland China and Hong Kong, and between Mainland China and Macau, but not between Hong Kong and Macau. Furthermore, each of the three regions circulates a local currency subject to its own exchange rate policy, with Hong Kong Dollar and Macau Pataca currently pegged to the US Dollar. These affect the mobility of trade and capital flows in the area. Hence, this paper applies the widely-used price-based approach due to Cheung et al. [5] to analyze the degrees of real and financial integration in the GBA based on interest rates, exchange rates, and price indexes data from January, 2016 to November, 2021. The real interest differential (RID), uncovered interest differential (UID) and the deviation from purchasing power parity (PPD) between each regional pair have means that are statistically and economically close to zero, implying high real and financial integration in the GBA. The unit root tests for stationarity also confirm that the time series are mean-reverting, so the economic integration in the GBA in the long run is foreseeable.
0 citations (Crossref) [2023-03-15]
Keywords: Economic development policy; Economic integration; Financial Integration; Greater Bay Area

The future of Cosmetics Advertisement Strategy: A Neuromarketing Study using Electrodermal Activity (EDA) as a measure of Emotional Arousal - Neto, Andreia; Lobo Marques, Joao Alexandre (2022 13th International Conference on E-business, Management and Economics, 2022)
Neuromarketing lies at the intersection of three main disciplines: psychology, neuroscience, and marketing, and it has been a successful neuroscientific approach for the study of real-life choices such as consumer behavior [1]. A current gap in the cosmetics field is the lack of published research studies, considering the marketing investment done yearly in this category. With the rapid economic expansion and the rise of social media in China, consumers' interest in beauty is growing. Even though the Chinese cosmetics sector is rapidly expanding, no studies have been done with Chinese consumers. This study aims to employ the same approach as previously done in consumer neuroscience studies to evaluate cosmetic brands' marketing strategy to understand better if immediate emotional responses can be measured using Electrodermal Activity (EDA). Here, we focus on cosmetics products advertisement as a model to understand consumer preference formation and choice. Eighteen Chinese female consumers were recruited between 19 and 37 years old. From the results obtained, it was understood that none of the participants have voted for the product advertisement for which they showed higher emotional arousal. However, it appears that the participants' preference is for the products for which the brand awareness is stronger since the product advertisements with more votes are the ones for the Korean brand used. The product advertisements with Asian faces were the ones with more votes, suggesting that Asian faces have engaged consumer preference. However, the product advertisements for the Brazilian brands, unknown to the Chinese public, were the ones with fewer votes, although, those product advertisements were the ones with more emotional arousal per minute. Those advertisements were also those with non-Asian faces, suggesting that this feature influenced voting decisions. From this study, it has been observed that Electrodermal Activity is a measure of emotional arousal that by itself cannot be translated into consumer engagement. Therefore, it is also proposed to evaluate brand awareness in future studies related to product advertisements. The physical features of the people included in the advertisements is also suggested to be further evaluated in future studies since a different cultural background seems to influence the consumers' engagement. Furthermore, using EDA to complement other neurophysiological tools like facial expression analysis is also suggested for future studies to have evidence about the nature of the emotions raised.
Keywords: advertisement; consumer behavior; consumer neurosciences; cosmetics; marketing; neuromarketing

Entrepreneurial Process of SMEs in Macau - Phillips, Jenny O. L.; Oliveira, Nelio (2022 13th International Conference on E-business, Management and Economics, 2022)
In recent years, entrepreneurship and innovation have been highly propagandised for Macau's economic development, diversification, and the Greater Bay Area (GBA). Since 2013, efforts have been exerted by the Macau government to encourage and support entrepreneurship, from the launching of the Young Entrepreneurs' Aid Scheme in 2013 and the Macau Young Entrepreneur Incubation Centre in 2015. While the failure rate of startups has been considered high in most parts of the world, the rate was only as low as 14% in Macau, with many businesses created every year. This research aims to study the unique entrepreneurial environment for small-to-medium enterprises (SMEs) starting up in Macau from the experience of local entrepreneurs who are benefactors of government support. In-depth interviews were conducted to understand the experience and perceptions of these entrepreneurs as they go through each stage of the entrepreneurial process. Existing research on entrepreneurial processes varies from the two-stage process, which focuses on the beginning of an enterprise, to the different models of various stages from ideas generation to exit or long-term development. From the consolidation of the literature on the entrepreneurial process, five key stages were taken to guide this qualitative research. Findings suggested that idea validation at the start of the entrepreneurial process is almost non-existent amongst our research subjects. Yet it does not affect the implementation and growth of these SMEs. The growth strategies tend to be steady and for the long term, with most SMEs having no consideration of an exit plan.
0 citations (Crossref) [2023-03-15]
Keywords: Economic diversification; Entrepreneurial process; Government entrepreneurship aids

The Application of Nudge Theory in Ensuring Change Acceptance in the Hospitality-Gaming Industry – A Case Analysis from Macau SAR, China - Tagulao, Thea Clarice Saavedra; Marques, Joao Alexandre Lobo (2022 13th International Conference on E-business, Management and Economics, 2022)
As the rate of change increases exponentially, organizations must adapt quickly to the business landscape's volatility, uncertainty, complexity, and ambiguity (VUCA). As a result, organizations must implement agile strategies and practices to ensure their responsiveness and readiness to any changes brought about by internal or external factors. With a greater number of changes, change agents are tasked with implementing various change management methodologies to ensure that change recipients accept change initiatives. This research will look at one of the methodologies used by change agents, the use of nudges from Thaler and Sunstein's Nudge Theory, which is a subtle intervention to influence an individual's decision-making with the goal of steering them towards a specific desired outcome; and analyze their effectiveness towards the change recipients when implemented. Change agents were interviewed on the application of Nudge Theory to change recipients when managing to change initiatives within their respective organizations. The results indicate that the use of nudges created by the change agents can significantly impact the level of resistance from the change recipients. If used correctly, the Nudge Theory can mitigate change resistance, and the success of a change initiative is higher. But, if change recipients are forced to comply, their resistance will be greater, affecting the organization overall.
0 citations (Crossref) [2023-03-15]
Keywords: Change Initiatives; Change Resistance; Nudge Theory; Organizational Behavior; Organizational Change Management

Consumers' Adoption of Molecular Chinese Medicine (MCM) in Macau: A Value-based approach - Hong, Chi Kit; Lampo, Alessandro (Proceedings of the 17th International Conference of the Academy of Global Business Research and Practice (AGBRP 2022), 2022)
Molecular Chinese Medicine (MCM) is a recent method of manufacturing and dosing prescriptions that brings several advantages when compared with Traditional Chinese Medicine (TCM). For instance, MCM is highly dissoluble, tastes better than the usual decoction, and the active principles are easily absorbed. Also, the manufacturing process is subject to better quality control. In spite of these benefits, consumers' intentions remain unclear due to the novelty of this technique. Therefore, an assessment of individuals' perceptions is relevant since molecular medicine is redefining how scientists understand and treat diseases, and it can be considered a medical innovation. To fill the research gap, the Value-based Acceptance Model (VAM) (Kim et al., 2007) is used to assess the individuals' perceptions of value and intention to accept MCM. Data from a sample of Macau residents are analyzed by means of structural equation modeling (SmartPLS). The results support the use of the model in our context, thus extending the applicability of the VAM to other settings. Except for 'technicality', the constructs of 'usefulness', 'enjoyment', and 'perceived fee' had a significant impact on the overall 'perceived value' of MCM, and in turn on the behavioral intention to use the innovation. To facilitate the diffusion of this dosage method in the marketplace, it is suggested that communications strategies consider the proposed sources of value when promoting MCM. To further explain the adoption process, it is recommended to include additional factors that may affect consumers' intention to adopt the innovation and extend the analysis to the actual usage.
Best Research Paper Award: https://www.usj.edu.mo/en/news/fbl-student-hong-chi-kit-and-prof-alessandro-lampo-received-the-best-research-paper-award-at-the-17th-international-conference-of-agbrp/